DETEKSI DAN KUANTIFIKASI RHODAMIN B PADA PRODUK LIPSTIK TANPA NOMOR NOTIFIKASI BPOM YANG BEREDAR DI PASAR MALAM KECAMATAN PALARAN SAMARINDA - juliyanti juliyanti; Umul Karimah; Lina Apriyani (Universitas Nahdlatul Ulama Kalimantan Timur, 2022)
Rhodamine B is one of chemical compound that is the most widely used in lipstick sold in have no a notification number from the drug and food regulatory agency, with physical characteristics that have a very light color and then when applied to the skin it is difficult to remove the traces. This research purposed to determine the presence of Rhodamine B in lipstick from the characteristics of lipstick containing Rhodamine B and to know the concentration of Rhodamine B in the sample. The method used in this study is qualitative and quantitative, with the selection of samples by purposive sampling. Qualitative identification in this study using a Rhodamine B test kit, meanwhile quantitative identification using UV-Vis Spectrophotometry. The results of the qualitative test using the Rhodamine B Test Kit contained 4 positive samples, sample 3,4,5 and 7. Rhodamine B concentration in positive samples were 34.76 ppm (sample 3), 38.30 ppm (sample 4), 74.28 ppm (sample 5), and 108.38 ppm (sample 7). Based on the qualitative analysis, the number concentration of Rhodamine B in the sample did not affect the color of the lipstick product, thus these samples were difficult to identify sample containing Rhodamine B. The results of this study indicated that there are still cosmetic manufacturers using the Rhodamine B as dye in lipstick production. Moreover, these positive samples do not meet the criteria for safe cosmetic products in terms of packaging, incomplete labels, heterogenous texture. Keywords: Lipstick, Rhodamine B, Spectrophotometry Uv-Vis, Test kit